Optimization of a Methodology for Quantification and Removal of Zinc Gives Insights Into the Effect of This Metal on the Stability and Function of the Zinc-Binding Co-chaperone Ydj1 - de Jesus, Jemmyson Romário; Aragão, Annelize Zambon Barbosa; Arruda, Marco Aurélio Zezzi; Ramos, Carlos H. I. (Frontiers in Chemistry, 2019)
Ydj1, a class B J-protein (Hsp40) in yeast, has two zinc finger domains in each monomer and belongs to an important co-chaperone family that plays crucial roles in cells, such as recognizing and binding partially folded proteins and assisting the Hsp70 chaperone family in protein folding. Yeast cells with ydj1 deletion were less efficient at coping with zinc stress than wild-type cells, and site-directed mutagenesis studies that impair or delete the zinc finger region have confirmed the importance of this region to the function of Ydj1; however, little is known about whether the presence of zinc is critical for the function of the protein. To gain insights into the effect of zinc on the structure and function of Ydj1 without having to modify its primary structure, a method was developed and optimized to quantify and remove the zinc from the protein. Recombinant Ydj1 was produced and purified, and its zinc content was determined by ICP-MS. The result showed that two zinc atoms were bound per monomer of protein, a good indicator that all sites were saturated. To optimize the removal of the bound zinc, variations on chelating agent (EDTA, EGTA, 1,10-phenanthroline), chelator concentration, reaction time, pH, and temperature were tested. These procedures had no effect on the overall secondary structure of the protein, since no significant changes in the circular dichroism spectrum were observed. The most significant removal (91±2%, n=3) of zinc was achieved using 1,10-phenanthroline (1x10-3 mol L-1) at 37°C with a pH 8.5 for 24 h. Zinc removal affected the stability of the protein, as observed by a thermal-induced unfolding assay showing that the temperature at the middle of the transition (Tm) decreased from 63±1°C to 60±1°C after Zn extraction. In addition, the effect on the ability of Ydj1 to protect a model protein (luciferase) against aggregation was completely abolished after the Zn removal procedure. The main conclusion is that zinc plays an important role in the stability and activity of Ydj1. Additionally, the results highlight the medical importance of chaperones, as altered zinc homeostasis is implicated in many diseases, such as neurodegenerative disorders.